2020
DOI: 10.1088/1367-2630/abafe9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rashba-spin–orbit coupling on superconducting boron-doped nanocrystalline diamond films: evidence of interfacial triplet superconductivity

Abstract: Among the many remarkable properties of diamond, the ability to superconduct when heavily doped with boron has attracted much interest in the carbon community. When considering the nanocrystalline boron doped system, the reduced dimensionality and confinement effects have led to several intriguing observations most notably, signatures of a mixed superconducting phase. Here we present ultra-high-resolution transmission electron microscopy imaging of the grain boundary and demonstrate how the complex microstruct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…At the zero frequency, P r has a peak at the origin or zero detune time (like the weak localization phenomena observed in the magnetic field-dependent resistance of metal with the effect of RSOC). This becomes a minimum by the application of the Rabi frequency which is like weak anti-localization [ 31 ]. This is a hallmark feature of RSOC in a topologically protected material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the zero frequency, P r has a peak at the origin or zero detune time (like the weak localization phenomena observed in the magnetic field-dependent resistance of metal with the effect of RSOC). This becomes a minimum by the application of the Rabi frequency which is like weak anti-localization [ 31 ]. This is a hallmark feature of RSOC in a topologically protected material.…”
Section: Discussionmentioning
confidence: 99%
“…A three-qubit system produces a similar effect to Rashba spin–orbit coupling (RSOC) and vortex structures in materials which are highlighted in the paper [ 26 , 27 , 28 ]. There have been attempts to acquire the geometric phase in a qubit circuit of IBM QE [ 21 , 29 , 30 , 31 ]. P r shown in Figure 1 b–e is defined as the probability of the desired state (most often, the initial state) after measurement.…”
Section: Introductionmentioning
confidence: 99%
“…This finding hints at the potential for superconductivity and superparamagnetism 22 . Additionally, research has shown that an interfacial grain boundary network in boron-doped nanocrystalline diamond films induces strong localized spin-orbit coupling, which results in conduction occurring in a triplet state 23 . Overall, the precise regulation of doping and control over the formation of mixed-phase defects in nanocrystalline diamond structures have garnered significant interest in recent years.…”
Section: Introductionmentioning
confidence: 99%